Hybrid Sterility And Role Of Wide Compatibility Variety In Different Genetic Backgrounds Of Rice (Oryza Sativa L.) Under Temperate Conditions Of Kashmir (Applied Biological Research, 2011)
The exploitation of pronounced heterosis in crosses between indica and japonica sub species of the  Asian cultivated rice (Oryza sativa L.) has been limited by hybrid sterility, which has been recognized  as one of the basis for speciation and genetic differentiation (Ouyang, 2009). Identification and use of  WC genes (wide compatibility varieties) have been found effective in overcoming the hybrid sterility  problem (Liu et al., 1996; Zhang et al., 1997). Inter-subspecific hybrids of rice have been developed  since an early attempt in China (Yuan, 1994). Similar kind of attempt was made under temperate  Kashmir conditions to get generate preliminary information about the genetic relatedness among  different genotypes available at the germplasm base of RRRS, Khudwani. Moreover, the study was  aimed to determine the role of genetic background of different genotypes for hybrid sterility and  possible overcome using one WCV genotype.
Keywords: Hybrid Sterility; Compatibility; Genetic Backgrounds